Modelling the effect of changing point systems to teams’ competition standing in a Malaysian soccer super league - Mat Yusof, Muhammad; Khalid, Ruzelan; Abdul Hamid, Mohamad Shukri; Mansor, Rosnalini; Sulaiman, Tajularipin (Bioinfo Publications, 2018)
In a sports league such as in a soccer league, the teams' competition standing is based on a cumulative point system. Typically, the standard point system is given to every single match for win, draw and lose teams is the 3-1-0 point system. In this paper, we explore the effect of changing point systems to teams' competition standing by changing the weightage values for win, draw and lose teams. Three types of point systems are explored in our soccer simulation model; firstly the 3-1-0, secondly the 2-1-0 and thirdly the 4-1-0 point system. Based on the teams participating in a Malaysian soccer Super League, our simulation result shows that there are small changes in term of teams' competition standing when we compared the actual rank and the simulation rank position. However, the 4-1-0 point system recorded the highest Pearson correlation value which is 0.97, followed by the 2-1-0 point system (0.95) and thirdly the 3-1-0 point system (0.94).